Various scenarios prediction of Contraflow operation under heterogeneous traffic condition by using VISSIM microscopic simulation - Jehad, A.E.; Ismail, A.; Borhan, M.N.; Ishak, S.Z. (International Journal of Engineering and Technology, 2018)
Prior studies showed that most evacuation contraflow designs have never been implemented. As a result, the effectiveness of these contraflow designs remains unknown. In this paper, VISSIM simulation has been used to achieve the possibility for predicting various scenarios at Kajang-Cheras highway contralane by using dynamic assignment model in order to establish best contraflow alternative path design operation. Method of Effectiveness (MOE) for dynamic assignment model (travel time, queue length, vehicles speed, delay time, fuel consumption, and CO emission) parameters has been analyzed first to assess the performance level of Contraflow operation. Seven alternative paths for the same contralane have been considered to achieve less travel time and queue length hence the reduction of fuel consumption and CO emissions that related to long queue length. Connector’s number 2 and 5 indicate the best alternative paths with the presence of the original connector (number 1) since contralane user realize that there are multi connectors to contralane ahead. Contraflow lane problems remain challenging for optimizing the best evacuation design system since the heterogeneous characteristics and no lane discipline domain on this highway at peak-hour. However, Contraflow freeway evacuation plan has been shown to be a successful remedy method to rapidly and efficiently move large numbers of vehicles during emergency situations.